2019
DOI: 10.1021/acs.langmuir.8b02796
|View full text |Cite
|
Sign up to set email alerts
|

Nanolamellar Tantalum Interfaces in the Osteoblast Adhesion

Abstract: The design of topographically patterned surfaces is considered to be a preferable approach to influence cellular behavior in a controllable manner, in particular to improve the osteogenic ability in bone regeneration. In the present study, we fabricated nanolamellar tantalum (Ta) surfaces with lamella wall thicknesses of 40 nm and 70 nm. The cells attached onto nanolamellar Ta surfaces exhibited higher protein adsorption and expression of β1 integrin, as compared to the non-structured bulk Ta, which would faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 62 publications
(145 reference statements)
0
15
0
Order By: Relevance
“…The interaction of cells with the implant surface mainly depends on the surface topographical features as well as chemical composition [ 38 ]. Adhesion of osteogenic cells to the substrate is crucial for the cell proliferation as well as differentiation on the implant [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of cells with the implant surface mainly depends on the surface topographical features as well as chemical composition [ 38 ]. Adhesion of osteogenic cells to the substrate is crucial for the cell proliferation as well as differentiation on the implant [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Ta coating and Ta 2 O 5 thin film are the main forms of research on Ta in vitro. For Ta, topographic surface design, especially nanoscale chemistry and morphology, is conducive to protein adsorption, which will promote cell proliferation and differentiation, especially the enhancement of bone regeneration ability [77,78]. Quartz crystal microbalance (QCM-D) is a unique technique to measure the adsorption capacity and viscoelasticity of proteins on the metal surface, which can be used to infer the orientation and conformation changes of adsorbed proteins [79,80].…”
Section: Protein Adsorption Experimentsmentioning
confidence: 99%
“…All these changes in the surface properties to form 25 nm sized nanopores favored fibroblast adhesion, proliferation and spreading, where surface properties of anodized nanofeatured materials, that is, surface chemistry, topography, hydrophobicity, and surface area, were influential on cellular functions (Toccafondi & Thorat, ; Wang et al, ; Zeng et al, ). Specifically, results showed increased surface roughness and higher surface areas for nanofeatured tantalum oxide surfaces compared to their nanosmooth counterparts, which provided more surface area for cellular interactions, and thus promoted enhanced cellular adhesion, proliferation and spreading on nanofeatured tantalum oxide surfaces (An et al, ; Stiehler et al, ; Wang et al, ). Additionally, the fact that NPT25 surfaces exhibited higher cellular density at 1, 3, and 5 days in vitro and higher cellular spreading compared to nonporous tantalum was in‐line with literature where hydrophilic surfaces promoted higher fibroblast adhesion and spreading compared to hydrophobic ones (Webb, Hlady, & Tresco, ).…”
Section: Discussionmentioning
confidence: 99%
“…Upon the nanoscale modification of tantalum, the surface properties, including surface chemistry, topography, energy, and so forth, would be altered, which in turn, improve cellular functions to enhance osseointegration with juxtaposed bone tissue (Balasundaram & Webster, ; Stiehler et al, ; Wang et al, ). For instance, An et al observed that osteoblast adhesion and proliferation on nanolamellar tantalum fabricated via equal channel angular pressing was higher compared to conventional tantalum having micrometer‐sized grains (An et al, ). Additionally, nanostructured tantalum coatings fabricated via ion implantation enhanced fibroblast adhesion in vitro , while reducing fibrous capsule formation and contracture in a mouse in vivo model (Park et al, ).…”
Section: Introductionmentioning
confidence: 99%